1987
DOI: 10.1111/j.1439-0310.1987.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Aversions of Starlings and Sparrows to Unfamiliar, Unexpected or Unusual Flavours and Colours in Food

Abstract: Captive starlings Sturnus vulgaris and house sparrows Passer domesticus were studied to explore the effects of previous experience on birds' aversions to quinine sulphate in blue‐coloured food. Daily food consumption and feeding behaviour were monitored for four groups of birds: (1) Control—birds trained to associate blue with quinine; (2) Unfamiliar—never having previously encountered blue or quinine; (3) Unexpected—trained to regard blue as palatable; (4) Anomalous—familiar with quinine in red, but not in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…For example, quinine sulfate, tannic acid and methiocarb have been found to be aversive in taste to House Sparrows (Greig- Moran, 2001;Clapperton et al, 2012;Day et al, 2012). These treatments may become more effective in combination with visual cues such as colouring seeds with colours that are aversive to House Sparrows (Greig-Smith, 1987;Clapperton et al, 2012). Other methods may decrease ability or preference for House Sparrow feeding including the selective breeding of plant characteristics to reduce feeding (Tipton et al, 1970;Khaleghizadeh, 2011).…”
Section: Impactsmentioning
confidence: 99%
“…For example, quinine sulfate, tannic acid and methiocarb have been found to be aversive in taste to House Sparrows (Greig- Moran, 2001;Clapperton et al, 2012;Day et al, 2012). These treatments may become more effective in combination with visual cues such as colouring seeds with colours that are aversive to House Sparrows (Greig-Smith, 1987;Clapperton et al, 2012). Other methods may decrease ability or preference for House Sparrow feeding including the selective breeding of plant characteristics to reduce feeding (Tipton et al, 1970;Khaleghizadeh, 2011).…”
Section: Impactsmentioning
confidence: 99%
“…For birds that may still consume treated corn seed, standard agronomic practices such as coloring the seed and planting at depth may reduce exposure. Commercially treated seeds, such as clothianidin treated corn, are colored with a dye which previous studies have found may reduce the attractiveness of treated seeds that go undetected by a grower and remain on the surface after planting ( Pank, 1976 ; Greig-Smith, 1987 ). Further, corn seeds are planted at depth (typically 38–51 mm below the soil surface to maximize root development) and therefore only seeds not appropriately planted (drilled) by equipment or spilled during loading of equipment and not cleaned up are expected to be available on the surface for consumption by birds.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of several repellents on the feeding behaviour of house sparrows have been investigated previously. Sparrows avoid familiar or novel food sources treated with chemicals reported as primary repellents, such as quinine sulfate, tannic acid, Optamint, d‐pulegone and cinnamamide 29, 30, 33, 34. They also assess foods on the basis of visual cues, avoiding black or blue food, and preferring to eat red, yellow or white foods 3, 21, 26.…”
Section: Introductionmentioning
confidence: 99%